Efetividade e segurança dos agentes antifator de necrose tumoral no tratamento da espondilite anquilosante no Sistema Único de Saúde - Pedro Ricardo Kömel Pimenta (2020)
Biological disease-modifying drugs (DMARDb) have revolutionized the treatment of ankylosing spondylitis (AS) in recent years. Studies demonstrate 30% to 50% effectiveness and good tolerance, the main adverse events being infectious symptoms and irritation at the application site (intravenous and subcutaneous parenteral medications. The aim of this study is to evaluate the effectiveness and safety of antiTNF in patients with AS Methods: This is a prospective cohort conducted at the pharmacy of the Regional Health Superintendence (SRS) of the Unified Health System (SUS) in Belo Horizonte, Minas Gerais, Brazil. The outcomes evaluated were the effectiveness of TNF by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), functionality by the Health Assessment Questionnaire (HAQ-DI), quality of life by the European Quality of Life Five dimensions (EuroQol-5D 3L) and the safe use of antiTNF at six and 12 months, linear regression was used to verify the factors associated with a better response by BASDAI Results: A total of 160 AS patients started treatment with anti-TNF. statistically significant improvement in disease activity, functionality and quality of life, with a reduction in the average of BASDAI and HAQ, in addition to an increase in the average of EQ-5D at 6 and 12 months (p <0.05). The drugs were well tolerated. Anti-TNF drugs were more effective in patients who did not use corticosteroids, had no comorbidities and had a better quality of life through the EQ5D at the beginning of the follow-up. Conclusion: This real-world study demonstrated that anti-TNF drugs are effective and well tolerated by patients with AS who seek the drug at SUS in Belo Horizonte.